2016
DOI: 10.1016/j.jaci.2015.08.018
|View full text |Cite
|
Sign up to set email alerts
|

Protein disulfide isomerase–endoplasmic reticulum resident protein 57 regulates allergen-induced airways inflammation, fibrosis, and hyperresponsiveness

Abstract: Background Evidence for association between asthma and the unfolded protein response (UPR) is emerging. ERp57 is an ER localized redox chaperone involved in folding and secretion of glycoproteins. We have previously demonstrated that ERp57 is up regulated in allergen-challenged human and murine lung epithelial cells. However, the role of ERp57 in asthma pathophysiology is unknown. Objectives Here, we sought to examine the contribution of airway epithelial-specific ERp57 in the pathogenesis of allergic asthma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
60
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 43 publications
(63 citation statements)
references
References 50 publications
2
60
1
Order By: Relevance
“…Moreover, the activation of XBP-1 has been shown to increase the levels of IL-6 in alveolar macrophages from patients with cystic fibrosis (39). In addition, our laboratory has demonstrated that the HDM-induced ER stress is linked to increased CCL20 and IL-6 in wild-type mice (23). Furthermore, the proinflammatory cytokines (IL-6), Th2 cytokines (IL-13 and IL-4), Th17 cytokines (IL-17A), and chemokines, including CCL20, KC, and G-CSF, have been shown to play a critical role in the pathogenesis of allergic airway disease (1,7,18,47,48,64).…”
Section: Discussionmentioning
confidence: 88%
See 4 more Smart Citations
“…Moreover, the activation of XBP-1 has been shown to increase the levels of IL-6 in alveolar macrophages from patients with cystic fibrosis (39). In addition, our laboratory has demonstrated that the HDM-induced ER stress is linked to increased CCL20 and IL-6 in wild-type mice (23). Furthermore, the proinflammatory cytokines (IL-6), Th2 cytokines (IL-13 and IL-4), Th17 cytokines (IL-17A), and chemokines, including CCL20, KC, and G-CSF, have been shown to play a critical role in the pathogenesis of allergic airway disease (1,7,18,47,48,64).…”
Section: Discussionmentioning
confidence: 88%
“…Airway remodeling is characterized by abnormal subepithelial collagen deposition along airway walls, smooth muscle hypertrophy, epithelial cell hyperplasia, mucus metaplasia, and basement membrane thickening (22). Increased levels of the profibrotic growth factor TGF-␤, collagen, and ␣-SMA in the lung drive airway fibrosis (23,56). Our results showed that TUDCA in both the preventive regimen and therapeutic regimen with subsequent HDM rechallenge significantly decreased collagen/hydroxyproline content and peribronchiolar fibrosis in the lungs of HDM-challenged mice.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations